A strategic R&D investment with flexible development time in real option game analysis - Giovanni Villani (Center for Economic Studies and ifo Institute (CESifo), 2009)
The real option theory provides a useful tool to evaluate an R&D investment under uncertainty because, unlike the NPV (Net Present Value), it considers the managerial flexibility that may be expand the investment opportunity value. However, most R&D investment projects are open to competing firms in the same industry or line of business, and so the strategic considerations become extremely important. In this paper we analyze a real option game between two firms that invest in R&D. The firm that invests first, defined as the Leader, acquires a first mover advantage that we assume as a higher market share than other one, namely the Follower, that postpones its R&D investment decision. But, several R&D investments present positive externalities and so, the option exercise by the Leader generates an Information Revelation that benefits the Follower. Moreover, to value the flexibility time to realize the development phase, we consider the American-Exchange type options.
Keywords: G13; C72; C15; O32; D80; 330; American Exchange options; game theory; Montecarlo simulation; R&D; information revelation; Forschung; Investition; Realoption; Informationsverhalten; Innovationswettbewerb; Spieltheorie; Theorie